A new theoretical engagement framework for citizen science projects: using a multi-temporal approach to address long-term public engagement challenges. (1st October 2022) - Liñán, Sonia; Salvador, Xavier; Álvarez, Ana; Comaposada, Andrea; Sanchez, Laura; Aparicio, Nuria; Rodero, Ivan; Piera, Jaume
Abstract: Effective citizen engagement is generally accepted as one of the most important steps for the success of citizen science programs. However, there is a lack of a common theoretical framework for recruitment and most projects rely on intuition or trial-and-error to develop their engagement strategies. Effective citizen science engagement needs theoretical participation frameworks and the concurrent action of different engagement roles to implement the framework. Besides, we must consider the various short-term and long-term engagement needs of the communities involved in the project. Furthermore, citizen science platforms are evolving towards infrastructures with technical but also social components to ensure long-term engagement. In this study, we have developed and tested an engagement framework for environmental citizen science projects using a novel approach that combines strategies and theoretical models that have proven efficient in other disciplines, such as human behaviour change and persuasion. Our framework is based on four interconnected pillars that feed each other: theoretical engagement models for behavioural change; social design for citizen science platforms; strategies for maintaining volunteer motivation; and strategies to increment the volunteers' ability. The combination of these four pillars results in a framework that integrates both short-term and long-term interaction mechanisms. This multi-temporal approach ensures keeping volunteers motivated and engaged for long periods, a requirement for many citizen science-monitoring programs. In addition, the theoretical framework points out the benefits of considering citizen science projects as a collaboration between multiple stakeholders to ensure long-term engagement. These stakeholders include the volunteers, but also new roles such as enabling communities that act as a bridge between volunteers and academia. Specifically, we have successfully tested this framework in a marine citizen science case study that monitors urban beaches. Furthermore, together with the proposed framework, we provide specific guidelines to help managers to design tailored strategies for their citizen science projects.